Microvascular Haemostasis and the Effect of Local Stimulation and inhibition of Platelet Function. An Experimental Study in Rabbits - Bergqvist, D; Arfors, K.-E (Thrombosis and Haemostasis, 1976)
The local stimulation and inhibition of haemostatic plug formation was studied by local infusion and superfusion of different agents – ADP, thrombin, adenosine, heparin, prostaglandin E1 (PGE1) and laser injury. ADP and laser injury shortened venular haemostatic plug formation time whereas adenosine in the superfusate and PGE1 prolonged it. Thrombin infusion had no effect but thrombin in the superfusate significantly stabilised the haemostatic plugs. It is suggested that ADP released from red cells is the most potent stimulator for haemostatic plug formation in the rabbit mesenteric microcirculation.